Duševní vlastnictví - případ informačních technologií - Ždímal, Martin (2007)
This theses analyses necessity and legitimacy of existence of intellectual property rights, especially patents and copyrights. There is shown the true essence of these instruments as monopoly privilege. On case of information technology I demonstrate that these privileges are unreasonable and counterproductive in many cases. Analysis of “free software” alternative model proves that use of patents and copyrights is not a necessary condition of creation of intangible goods. The last part of this work shows, that existence of any special instruments for intangible goods protection is not needed as well as it is not reasonable